Reuben Fine autograph scores - Fine, Reuben, 1914-1993.; Keesing, L. Th.
Twelve notebooks containing autograph scores and photostats of autograph scores of Fine's games of chess. Also includes several autograph scores of games of L.Th. Keesing.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Photostats, in part.
Tournament chess player and psychoanalyst.
Collection material in English.
Keywords: Chess; Chess players; Psychoanalysts